Reconstruction algorithm study of 2D interpolating resistive readout structure - 修青磊 董明义 刘荣光 张建 欧阳群 陈元柏 (Chinese physics C, 2013)
Systematic investigations including both simulation and prototype tests have been done about the interpolating resistive readout structure with GEM （Gaseous Electron Multiplier） detector. From the simulation, we have a good knowledge of the process of charge diffusion on the surface of the readout plane and develop several reconstruction methods to determine the hit position. The total signal duration time of a typical event with the readout structure was about several hundred nanoseconds, which implied an ideal count rate up to 106 Hz. A stable working prototype was designed and fabricated after the simulation. Using 55Fe 5.9 performance of the prototype was examined with flat field image and some special geometry energy resolution of about 17% was obtained. keV X-ray, the image shapes, meanwhile, an